2019
DOI: 10.1002/nme.6085
|View full text |Cite
|
Sign up to set email alerts
|

A scalable parallel finite element framework for growing geometries. Application to metal additive manufacturing

Abstract: Summary This work introduces an innovative parallel fully‐distributed finite element framework for growing geometries and its application to metal additive manufacturing. It is well known that virtual part design and qualification in additive manufacturing requires highly accurate multiscale and multiphysics analyses. Only high performance computing tools are able to handle such complexity in time frames compatible with time‐to‐market. However, efficiency, without loss of accuracy, has rarely held the centre s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 67 publications
0
36
0
Order By: Relevance
“…It was shown that this modeling method can correctly capture the thermal history as obtained using the thermocouples. More importantly, it was observed by Neiva et al [ 29 ] that the model correctly predicts the high temperatures measured near an overhanging feature. Therefore, it is deemed suitable for the intended purpose of identifying geometric features which cause local heat accumulation during the LPBF process.…”
Section: Reference Thermal Lpbf Process Modelmentioning
confidence: 67%
See 1 more Smart Citation
“…It was shown that this modeling method can correctly capture the thermal history as obtained using the thermocouples. More importantly, it was observed by Neiva et al [ 29 ] that the model correctly predicts the high temperatures measured near an overhanging feature. Therefore, it is deemed suitable for the intended purpose of identifying geometric features which cause local heat accumulation during the LPBF process.…”
Section: Reference Thermal Lpbf Process Modelmentioning
confidence: 67%
“…It is based on the thermal model previously presented by Chiumenti et al [ 27 ] for simulating material deposition in the laser material deposition (LMD) process. The same concept was later used for LPBF modeling in several publications [ 24 , 28 , 29 ]. The experimental validation of the model has been presented in Davies [ 24 ] where simulation results were compared with temperatures empirically recorded using in situ thermocouples placed inside the part during the LPBF process.…”
Section: Reference Thermal Lpbf Process Modelmentioning
confidence: 99%
“…The mechanical parameters, i.e. Poisson's ratio ν, Young's modulus E and yield limit σ y , are taken from the literature, see [32,36,46]. The hardening modulus H sol is, at this stage, chosen without particular literature reference.…”
Section: Numerical Examplesmentioning
confidence: 99%
“…The thermal material parameters, i.e. the expansion coefficient α, the specific heat capacity c, the conductivity k and the latent heat L, as well as the initial temperature θ ini and the reference temperature θ ref are parameters based on [32,36]. The respective effective counterparts which are used to calculate the material response follow from the homogenisation approach introduced in the previous chapters in contrast to material models which directly incorporate temperature-dependent averaged material properties.…”
Section: Numerical Examplesmentioning
confidence: 99%
“…A lot of past AM simulations involve very small deposits or have approximated the process due to the high cost of the simulations. Due to this fact more recent articles have started using advanced numerical methods to allow for less costly simulations, this includes multi-scale approaches [8] and remeshing approaches [9] [10].…”
mentioning
confidence: 99%